Analysis of Educational Leadership Development at Salman Al Farisi Integrated Islamic School Yogyakarta - Fauziah Andini; Dwi Esti Andriani (Green Publisher Indonesia, 2024)
The demands of changing times in the world of education are certainly felt by education in Indonesia. Currently, the hot topic in education is the mobilising teacher. The purpose of this teacher mobiliser is very much in line with the purpose of the professional learning community, which is a collection of teachers who are required to be moved, move and mobilise in contributing to achieving learning that is liberating and in favour of students. Actually, this learning community has long existed in education in Indonesia. Like the case study that the author conducted at SDIT Salman Al Farisi. This PLC or professional learning community is also implemented by the principal and teacher employees. This Professional Learning Community at SDIT Salman Al Farisi Yogyakarta can be drawn a line about the advantages of the PLC programme here, namely that the Principal is very active in participating in professional learning community activities.